Synthesis of pewter alloy from tin–copper–antimony powder mixtures by microwave and conventional sintering - Gabbitas, Brian Leslie; Mohamed Ariff, Tasnim Firdaus; Cao, Peng (Maney Publishing, 2010)
Two compositions of pewter alloy were sintered using both microwave and conventional vacuum sintering, and the effects of sintering time, temperature and weight percentage of copper and antimony on the mechanical and structural properties were examined for both sintering methods. Microwave sintered samples had finer microstructures, higher densities, higher hardness and tensile strength compared to the conventionally sintered samples and traditionally cast pewter. By increasing the copper and antimony contents, higher hardness was achieved. Better mechanical properties were found after microwave sintering after shorter sintering times compared with conventional sintering, but longer sintering times resulted in better diffusion for both sintering methods. The microwave sintered samples in general were capable of achieving similar amounts of diffusion to those conventionally sintered for the same time. But the total sintering process is much faster in microwave heating than in conventional heating due to the rapid heating effect.